A REVISTA, O DESIGN GRÁFICO E A TIPOGRAFIA DIGITAL: um estudo de caso sobre as capas de Elle - DUARTE, AUDREY MARQUES (2017)
The growing technology evolution in society - along with the demands boosted by desires and needs expressed by receivers of messages - requires analyses about what is happening in communicational processes, since the reading audience is demonstrating more attention to visual messages not only concerning their quality, but also to what they are presented (images increasingly replacing texts). Here, we find our moment, the contemporariness of our study, the interaction between communication, graphic design, technology, digital environment and magazines – specifically the covers of the Elle Brasil magazine, with the changes we have observed in visual communication components, such as, in our case, in the typography. Our goal was to explore the environment of digital typography, analyzing its presence in the covers of Elle Brasil, and find criteria that offered conditions to help controlling the typographic presence in digital platforms. As methodology, we conducted a qualitative exploratory and descriptive research, like a case study, using the analysis of content on the method of presentation of digital typography in the covers of Elle Brasil available in different devices, selecting categories that allowed an observation of the relation between the display features and the design where the typography is present. Additionally, an extensive bibliography research and a semi-structured interview with an expert were conducted to deepen the topic addressed in this thesis. Based on analyses and indications, our main argument is that it is possible to established criteria to check the quality control for the typography presence in the digital environment, considering the characteristics of the platforms and the identity of the media outlet, so that the same typography used offline or offline does not lose readability and legibility. Even if the transition to digital devices leads the typography to conflicts, the presence of usability in the devices corrects the discomfort and makes it satisfactory.